Changes in Drp1 Function and Mitochondrial Morphology Are Associated with the α-Synuclein Pathology in a Transgenic Mouse Model of Parkinson’s Disease - Philipp Portz; Michael K. Lee (Cells, 2021)
Alterations in mitochondrial function and morphology are associated with many human diseases, including cancer and neurodegenerative diseases. Mitochondrial impairment is linked to Parkinson’s disease (PD) pathogenesis, and alterations in mitochondrial dynamics are seen in PD models. In particular, α-synuclein (αS) abnormalities are often associated with pathological changes to mitochondria. However, the relationship between αS pathology and mitochondrial dynamics remains poorly defined. Herein, we examined a mouse model of α-synucleinopathy for αS pathology-linked alterations in mitochondrial dynamics in vivo. We show that α-synucleinopathy in a transgenic (Tg) mouse model expressing familial PD-linked mutant A53T human αS (TgA53T) is associated with a decrease in Drp1 localization and activity in the mitochondria. In addition, we show that the loss of Drp1 function in the mitochondria is associated with two distinct phenotypes of enlarged neuronal mitochondria. Mitochondrial enlargement was only present in diseased animals and, apart from Drp1, other proteins involved in mitochondrial dynamics are unlikely to cause these changes, as their levels remained mostly unchanged. Further, the levels of Mfn1, a protein that facilitates mitochondrial fusion, was decreased nonspecifically with transgene expression. These results support the view that altered mitochondrial dynamics are a significant neuropathological factor in α-synucleinopathies.